Seasonal changes in the vertical structure of ozone in the Martian lower atmosphere and its relationship to water vapour - Temperature and GCM data used - Olsen, K; Fedorova, A; Forget, F (University of Oxford, 2022)
Temperature data derived from ACS NIR observations of Mars used in the paper: Seasonal changes in the vertical structure of ozone in the Martian lower atmosphere and its relationship to water vapour. LMD GCM data interpolated to the terminator (T/P/density/H2O/O3) used in the paper: Seasonal changes in the vertical structure of ozone in the Martian lower atmosphere and its relationship to water vapour.